When ‘service with a smile’ is not enough: a systematic review of emotional labour in the service encounter - Nunan, Daniel (Cranfield University, 2005)
Recently, there has been increasing research into how emotion is displayed in an organisational context, as the creation of emotional links with consumers becomes more critical in developing strong brands. Emotion is a seductive concept, ubiquitous and powerful, yet often poorly understood. Adopting a systematic review method I use the framework of emotional labour as a basis for examining the role of emotion in service encounters, and understanding how emotional labour contributes to consumer evaluations of service quality. Traditional views of emotional labour have focussed on low paid, routine, interactive service work, such as in the retail, travel, and leisure industries. As a result, it is argued, emotional labour is undervalued by employers. Through a review of empirical and conceptual literature on emotional labour evidence suggests that emotional labour is significant in a wide range of professional and non-professional service roles, and has both negative and positive consequences. However, in many brief service encounters in routine service interactions ‘service with a smile’ was not seen to be a significant contributor to consumer satisfaction. Conversely, in many professional roles effective use of emotional labour was related to positive evaluations of technical service quality. Several research gaps within emotional labour are identified, including research into crosscultural and multi-channel environments. A significant theme in the empirical evidence was of employee emotional autonomy being an important factor in the correct performance of emotional labour. I provide a conceptual model of emotional labour that moves the focus away from the employee to a more consumer-focussed dyad, reflective of a service encounter. I propose that effective emotional linkages are formed through interactions based on emotional labour. This implies that if organisations genuinely wish to form strong emotional bonds with consumers, they must be willing to give greater emotional autonomy to service employees.